Factors Influencing Work Motivation of Nurses in military Hospitals Dr. Midiyato Suratani Tanjungpinang - Deby Zulkarnain Rahadian Syah; Budi Anna Keliat; Hanny Handiyani; Eva Eva; Agnes Defi; Agnes Rini; Susana Helen Tanlain (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This study identified the factors that influence nurses' work motivation. The method used is quantitative analysis with a questionnaire instrument of respondent characteristics, leadership style, and nurse work motivation. The respondents were 65 nurses at the Dr. Midiyato Suratani Tanjungpingang Hospital. Univariate results showed that most of the respondents were women at 92,3%, education level was 60% D3 Nursing, employee status was 53,8% PNS, length of service was 11 to 15 years 38,5%, and the average age was 36 years. The results of the bivariate test of leadership style affect work motivation with a p-value of 0,001, the highest perception of leadership style is consultative with a mean of 107.5. That which has the highest impact on motivation with a mean of 110,8 is a democratic leadership style. Meanwhile, age does not affect motivation with a p-value of 0,486, including an education p-value of 0,533. Employee status affects motivation with a p-value of 0,002, then the length of work with a p-value of 0,039. The results of the multivariate analysis showed that employee status had the most significant effect on the work motivation of nurses 0,006. The conclusion is that the status of civil servants is the main motivation for nurse performance rather than leadership style, age and length of service. It is suggested to the hospital that the status of employees who are still PTT can be appointed as civil servants, then for the head of the nursing room can use a democratic leadership style to increase the work motivation of the nurses. Abstrak: Penelitian ini mengidentifikasi faktor-faktor yang memengaruhi motivasi kerja perawat. Metode yang digunakan adalah analitik kuantitatif dengan instrumen kuesioner karakteristik responden, gaya kepemimpinan, dan motivasi kerja perawat. Jumlah responden adalah 65 orang perawat pelaksana di RS Angkatan Laut Dr. Midiyato Suratani Tanjungpingang. Hasil univariat didapatkan responden sebagian besar perempuan sebesar 92,3%, tingkat pendidikan 60% D3 Keperawatan, status pegawai 53,8% PNS, lama kerja 11 sampai 15 tahun 38,5% dan umur rata-rata 36 tahun. Hasil uji bivariat gaya kepemimpinan memengaruhi motivasi kerja dengan p value 0,001 dan persepsi tertinggi gaya kepemimpinan adalah konsultatif dengan mean 107,5, dan yang berdampak pada motivasi tertinggi dengan mean 110,8 adalah gaya kepemimpinan demokratik. Adapun usia tidak memengaruhi motivasi dengan p value 0,486, termasuk pendidikan dengan p value 0,533. Status pegawai memengaruhi motivasi dengan p value 0,002, kemudian lama kerja dengan p value 0,039. Hasil analisis multivariat didapatkan status pegawai paling signifikan memengaruhi motivasi kerja perawat 0,006. Kesimpulannya adalah faktor status pegawai menjadi PNS merupakan motivasi kinerja perawat yang utama daripada gaya kepemimpinan, usia dan lama kerja. Disarankan kepada pihak rumah sakit bahwa status pegawai yang masih PTT bisa diangkat menjadi PNS, kemudian bagi kepala ruangan keperawatan dapat menggunakan gaya kepemimpinan demokratik untuk meningkatkan motivasi kerja perawatnya